Confirmation by solid-state NMR spectroscopy of a strong complex phenol-dietary fiber with retention of antioxidant activity in vitro. (May 2020) - Bermúdez-Oria, Alejandra; Rodríguez-Gutiérrez, Guillermo; Fernández-Prior, África; Knicker, Heike; Fernández-Bolaños, Juan
Abstract: The aim of this study was to prepare a complex between the olive phenolic compounds, hydroxytyrosol (HT), 3, 4-dihydroxyphenylglycol (DHPG) and their mixture, with the soluble and insoluble dietary fiber of apple cell wall. A strong interaction between phenols and the apple cell wall occurred during the drying phase and it was confirmed by ultraviolet–visible spectrometry, Fourier transform infrared spectrometry, differential scanning calorimetry, thermogravimetry and especially by solid-state 13 C NMR spectroscopy. The antiradical activity by DPPH, ABTS and ORAC assays confirmed that the simple phenolic HT/DHPG maintained in part their antioxidant activity after complexation with the apple cell wall. In addition, the HT/DHPG-soluble and insoluble fractions obtained after simulated gastrointestinal fluids retained this antioxidant activity. These complexes may be protected from absorption during gastrointestinal transit to reach the colon. In the case of the soluble dietary fiber, an enzymatic treatment, in a simulation of hydrolysis by colonic microflora, released oligomers with potential antioxidant activity from this complex. Therefore, the intake of HT/DHPG bound to the fiber of apple cell wall could provide many of the health benefits associated with dietary fiber, and be fermented by gut bacteria to contribute to a healthy antioxidant environment. Graphical abstract: Image 1 Highlights: Complex formation of olive phenols with apple dietary fiber was suggested by NMR. Drying enhanced the interaction of HT/DHPG with soluble and insoluble fractions. Phenol-soluble and insoluble dietary fiber complexes showed antioxidant activity. Reduction of polysaccharide size enhanced the complex's antioxidant activity.